Penyelesaian Sengketa Tanah Dati (Studi Kasus Putusan MA Nomor 2025 K/Pdt/1983) - Priescillia Mariana Palapessy; Jenny Kristiana Matuankotta; Adonia Ivone Laturette (Faculty of Law, Universitas Pattimura, 2021)
Introductioan: Dati land can be lost if there are no more descendants as heirs. Dati disappears then the State Government can give it to other children of the country to own, but in its giving there are often disputes, so that parties who feel they have the right propose a settlement through court channels.Purposes of the Research: To study and explain the factors in the occurrence of Dati land disputes and settlement of Dati land disputes based on the Supreme Court Decision No.2025 K/Pdt/1983.Methods of the Research: This study uses normative legal research methods with the source of legal materials used in the study are primary, secondary and tertiary. Data collection carried out in the study is library research, namely analyzing library materials related to research.Results of the Research: Based on the results of the study, there were various factors that influenced the occurrence of dati land disputes, but what happened between the Plaintiff and the Defendant was that mutual claims on dati land disappeared from the Head of Dati Estefanus Wattimena. Based on the evidence presented in the trial, the judge decided that Batubulan and Telagaraja dati belonged to the Defendant which was given by the State Government to the Defendant’s grandfather in 1923 as a form of remuneration for the development of the Urimessing State, and that the Defendant in good faith had cultivated the land for decades, so that with that the Plaintiff was unable to weaken the evidence from the Defendant.